Uso de sustrato de cascarilla de arroz y arena de río en la producción de plántulas de tabaco bajo sistema de bandejas flotantes en Tarapoto - Rivera Delgado, David (2004)
This research work was developed, in the premises of the tobacco company's del PERU S. A. (TAPESA), located in Juan Guerra district. The experimental design used is a design complete random (DCA) with five treatments and a witness with bromide methyl, (10 days in anaerobic) T1, T2 (20 days in anaerobic), T3 {(30 días en anaerobiosis), T4 (40 days in anaerobic), T5 (01 day in anaerobic), cough results of this work are.} The T5 (01 day in the anaerobic), is the treatment with the least of insect, with excellent results in the control of plant diseases with the exception of the removal of rice seed; (40 days in anaerobic) T4 and T3 (30 days in anaerobic) treatment treatments that yielded the highest averages to the completion of assessments; the plant height (4.5 cm and 3.78 cm), diameter of the tree (3.85 cm and 4.03 cm), number of leaves (6.25 and 5.76 leaves), fresh weight and dry weight (4.30 g and 0.41 g) respectively. production of the lechuguino costs vary between 0.056 to 0.065 soles per seedling among the studied treatments; the production of tobacco in floating trays (hydroponics) seedling is a viable technical and ecological alternative to the use of methyl bromide.